Maternal depressive symptoms, sleep, and odds of spontaneous early birth: implications for racial inequities in birth outcomes. Issue 11 (21st May 2021) - Christian, Lisa M; Webber, Shannon; Gillespie, Shannon; Strahm, Anna M; Schaffir, Jonathan; Gokun, Yevgeniya; Porter, Kyle
Abstract: Study Objectives: Delivery prior to full term affects 37% of US births, including 400, 000 preterm births (<37 weeks) and >1, 000, 000 early term births (37–38 weeks). Approximately 70% of cases of shortened gestation are spontaneous—without medically-indicated cause. Elucidation of modifiable behavioral factors would have considerable clinical impact. Methods: This study examined the role of depressive symptoms and sleep quality in predicting the odds of spontaneous shortened gestation among 317 women (135 black, 182 white) who completed psychosocial assessment in mid-pregnancy. Results: Adjusting for key covariates, black women had 1.89 times higher odds of spontaneous shortened gestation compared to White women (OR [95% CI] = 1.89 [1.01, 3.53], p = 0.046). Women who reported only poor subjective sleep quality (PSQI > 6) or only elevated depressive symptoms (CES-D ≥ 16) exhibited no statistically significant differences in odds of spontaneous shortened gestation compared to those with neither risk factor. However, women with comorbid poor sleep and depressive symptoms exhibited markedly higher odds of spontaneous shortened gestation than those with neither risk factor (39.2% versus 15.7% [OR (95% CI) = 2.69 (1.27, 5.70)], p = 0.01). A higher proportion of black women met criteria for both risk factors (23% of black women versus 11% of white women; p = 0.004), with a lower proportion experiencing neither risk factor (40.7% of black versus 64.3% of white women; p < 0.001). Conclusions: Additive effects of poor subjective sleep quality and depressive symptoms were observed with markedly higher odds of spontaneous shortened gestation among women with both risk factors. Racial inequities in rates of comorbid exposure corresponded with inequities in shortened gestation. Future empirical studies and intervention efforts should consider the interactive effects of these commonly co-morbid exposures.